Penerapan Metode Fuzzy Tsukamoto dalam Menentukan Jumlah Produksi Opak pada Home Industri Tegar Jaya - Mahendra, Yusril Panca; Siahaan, R. Fanry (CV. RO BEMA, 2024)
Home Industry Tegar Jaya is one of the home industries that are included in the category of small and medium enterprises (MSMEs), which are engaged in the production of opaque. The high customer interest in opak makes Tegar Jaya Home Industries continue to improve their products, Tegar Jaya Home Industries often have difficulty determining the amount of production due to the uncertain number of requests that sometimes go up and down every month. This is also influenced by the COVID-19 virus pandemic, where the community's economy has made market demand unstable and fluctuating, demand can increase quite high and also experience a drastic decline. Therefore it is necessary to have a system that can determine the amount of production in order to minimize losses to the industry. The system is built using the PHP and MySQL programming languages. In the calculation process, the data taken is data in April 2022, namely 4325 kg of demand and 560 kg of supply, so that by using the Fuzzy Tsukamoto process, the calculation results of 3958 kg of opaque must be produced by the industry. The system that is built can run well and is very effective for the industry to determine the amount of production that is even better.